90.1k views
2 votes
How do you solve:

3(a+2)=2(a-7) and 9(t-1)=6(t+2)-t

User Uruk
by
5.8k points

2 Answers

5 votes
There are many many steps ,but the answer is t=3
User Agnieszka Polec
by
6.2k points
4 votes

Answer:

t=3

Explanation:

Simplifying

5 + -1(t + 3) = -1 + 2(t + -3) Reorder the terms:

5 + -1(3 + t) = -1 + 2(t + -3)

5 + (3 * -1 + t * -1) = -1 + 2(t + -3)

5 + (-3 + -1t) = -1 + 2(t + -3)

Combine like terms: 5 + -3 = 2

2 + -1t = -1 + 2(t + -3)

Reorder the terms:

2 + -1t = -1 + 2(-3 + t)

2 + -1t = -1 + (-3 * 2 + t * 2)

2 + -1t = -1 + (-6 + 2t)

Combine like terms: -1 + -6 = -7

2 + -1t = -7 + 2t

Solving

2 + -1t = -7 + 2t

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '-2t' to each side of the equation.

2 + -1t + -2t = -7 + 2t + -2t

Combine like terms: -1t + -2t = -3t

2 + -3t = -7 + 2t + -2t

Combine like terms: 2t + -2t = 0

2 + -3t = -7 + 0

2 + -3t = -7

Add '-2' to each side of the equation.

2 + -2 + -3t = -7 + -2

Combine like terms: 2 + -2 = 0

0 + -3t = -7 + -2

-3t = -7 + -2

Combine like terms: -7 + -2 = -9

-3t = -9

Divide each side by '-3'.

t = 3

Simplifying

t = 3

User Desire Kaleba
by
5.6k points